¿Puede atribuírsele valor estético a la música popular? Una postura frente a adorno - Singer, Deborah (2004)
Abstract. This essay is based on the theories of the German musician and critic Theodor W. Adorno (1903-1969), who assigned to music a key role as a forming (or deforming) agent of human conscience. From his point of view, “good music” (classical music, for instance) redeems the individual, while “bad music” tends to preserve the existing order alienates humans, depriving them from their critical capacity; jazz, pop music and other music genres fall into this last category and the they are not assigned any aesthetics value. The author analyzes Adorno's position and pleads in favor of popular music. In order to achieve this, she analyzes the aesthetics of music in small towns, folklore, and the origin and impact of modern rhythms such as rap music.